Cloning and functional characterization of an acyl-acyl carrier protein thioesterase (JcFATB1)from Jatropha curcas - Wu, P.Z.; Li, J.; Wei, Q.; Zeng, L.; Chen, Y.; Li, M.; Jiang, H.; Jiang, H.
A full-length cDNA of an acyl-acyl carrier protein (ACP)thioesterase (TE)(EC 3.1.2.14), named JcFATB1, was isolated from the woody oil plant Jatropha curcas L. The deduced amino acid sequence of the cDNA shares about 78
Keywords: FATTY ACID; PALMITATE